A versatile PDMS submicrobead/graphene oxide nanocomposite ink for the direct ink writing of wearable micron-scale tactile sensors. (September 2019) - Shi, Ge; Lowe, Sean E.; Teo, Adrian J.T.; Dinh, Toan K.; Tan, Say Hwa; Qin, Jiadong; Zhang, Yubai; Zhong, Yu Lin; Zhao, Huijun
Graphical abstract: Highlights: An aqueous nanocomposite ink with polydimethylsiloxane (PDMS) submicrobeads and an electrochemically derived graphene oxide (EGO) nanofiller was formulated for DIW. The DIW-printed device exhibits low resistivity (1660 Ω·cm) at a low percolation threshold of EGO (0.83 vol.%) owing to the unique nanocomposite structure of graphene-wrapped elastomeric beads. The printed large-scale strain sensors showed excellent performance over a large working range (up to 40% strain), with high gauge factor (20.3), and fast responsivity (83 ms). The micron-scale pressure sensors demonstrated high pressure sensitivity (0.31 kPa −1 ) and operating range (0.248–500 kPa). The interfacial effect in the DIW printed layers (layer-by-layer) has huge impact toward overall strain sensing resistance and mechanism. Abstract: Although direct ink writing (DIW) is a versatile 3D printing technique, progress in DIW has been constrained by the stringent rheological requirements for printable conductive nanocomposites, particularly at smaller length scales. In this work, we overcome these challenges using an aqueous nanocomposite ink with polydimethylsiloxane (PDMS) submicrobeads and an electrochemically derived graphene oxide (EGO) nanofiller. This nanocomposite ink possesses a thixotropic, self-supporting viscoelasticity. It can be easily extruded through very small nozzle openings (as small as 50 μm) allowing for the highest resolution PDMS DIW reported to date. With a mild thermal annealing, the DIW-printed device exhibits low resistivity (1660 Ω·cm) at a low percolation threshold of EGO (0.83 vol.%) owing to the unique nanocomposite structure of graphene-wrapped elastomeric beads. The nanocomposite ink was used to print wearable, macro-scale strain sensing patches, as well as remarkably small, micron-scale pressure sensors. The large-scale strain sensors have excellent performance over a large working range (up to 40% strain), with high gauge factor (20.3) and fast responsivity (83 ms), while the micron-scale pressure sensors demonstrated high pressure sensitivity (0.31 kPa −1 ) and operating range (0.248–500 kPa). Ultrahigh resolution, multi-material layer-by-layer deposition allows the engineering of microscale features into the devices, features which can be used to tune the piezoresistive mechanism and degree of piezoresistivity.